greatOplus (Extruded Blend of Flaxseed and Nannochloropsis oculata Biomass) Improves Finishing Cattle Performance and Carcass Characteristics - Firman Nasiu; Luis F.B.B. Feitoza; A. N. Baker; L. R. Thorn; Ludmila S. Monteiro; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2025)
Objective: This study investigated feeding greatOplus (GOP), an extruded mixture of flaxseed and Nannochloropsis oculata microalgae biomass (NBO3 Technologies LLC; Manhattan, KS) on feedlot cattle performance and carcass characteristics. Study Description: Yearling steers (n = 700; 825 lb ± 18.07 lb initial body weight (BW)) were blocked by initial BW and assigned randomly, within block, to 28 feedlot pens containing 25 animals/pen. Cattle were vaccinated against viral and clostridial pathogens and treated for internal and external parasites (Bovishield Gold 5, Ultrabac 7 Somubac, and Dectomax injectable; Zoetis Animal Health), and implanted with a combination implant (Component TE-200; Elanco USA). The control diet (CON) consisted of 58.3% steam-flaked corn, 20% wet corn gluten feed, 2.56% soybean meal, and 4.17% vitamin/mineral/feed additive premix. For the greatOplus (GOP; an extruded blend of flaxseed and Nannochloropsis oculata microalgae) diet, a portion of the corn and all the soybean meal were replaced with 10% GOP (dry basis) to create isonitrogenous diets. Cattle were fed once daily, ad libitum. After 175 days on feed, animals were weighed and transported to a commercial abattoir for harvest. Animal performance measurements included average daily gain (ADG), dry matter intake (DMI), and gain:feed (G:F). Hot carcass weight (HCW) and incidence of abscessed livers were assessed on the day of harvest, and marbling score, 12th rib fat thickness, longissimus muscle area, and U.S. Department of Agriculture (USDA) yield and quality grades were determined following 48 hours of refrigeration. Results: Cattle fed GOP had greater DMI and ADG (P < 0.05) compared to cattle fed CON, but G:F was not affected by treatment (P > 0.10). Cattle fed GOP had greater HCW compared to those fed CON (932.11 versus 902.79 lb; P < 0.01) and tended to produce more Prime and Choice carcasses (87.4 versus 83.0%; P = 0.11) with greater 12th rib backfat (0.61 versus 0.59 in; P < 0.02) and greater yield grades (2.91 versus 2.75; P < 0.01). Marbling score (488 versus 491), longissimus muscle area (14.6 versus 14.5 in2) and liver abscess incidence (12 versus 16% for CON and GOP, respectively) were unaffected by treatment (P > 0.10). Carcass values were calculated using base prices, premiums, and discounts published by the USDA, and were greater for cattle fed GOP compared to cattle fed the CON diet (2,122 versus 2,059; P < 0.01). The Bottom Line: Including greatOPlus at 10% of the diet dry matter improved cattle performance, largely as the result of its impact on DMI and ADG.
Keywords: greatOplus; animal performance; meat characteristics